2020
DOI: 10.18764/1981-6421e2020.13
|View full text |Cite
|
Sign up to set email alerts
|

EVIDENCE OF DYSTOCIA IN A FREE-RANGING COWNOSE RAY Rhinoptera bonasus (ELASMOBRANCHII, RHINOPTERIDAE)

Abstract: Capture and handling can have sublethal consequences on elasmobranchs, even when individuals are quickly released to comply with legislation or fishermen's ethics on voluntary conservation. Dystocia is characterized by the physical inability to deliver the neonate, even when it is ready for birth. So far, this phenomenon has been reported only in Cownose rays kept under human care. The present study aimed to report the occurrence of dystocia in a free-living Cownose ray (Rhinoptera bonasus), possibly caused by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Dystocia has been observed on multiple occasions for Cownose Rays in aquaria (Cavalcante et al, 2016;George et al, 2017), and it has also been suggested as a cause of mortality associated with capture for in situ rays (Leite et al, 2020). Procedures for cesarean delivery and monitoring have been developed for Cownose Rays, and, if adopted, should minimize neonate and female loss for animals in aquaria.…”
Section: Reproductive Pathologiesmentioning
confidence: 99%
“…Dystocia has been observed on multiple occasions for Cownose Rays in aquaria (Cavalcante et al, 2016;George et al, 2017), and it has also been suggested as a cause of mortality associated with capture for in situ rays (Leite et al, 2020). Procedures for cesarean delivery and monitoring have been developed for Cownose Rays, and, if adopted, should minimize neonate and female loss for animals in aquaria.…”
Section: Reproductive Pathologiesmentioning
confidence: 99%